The impact of ash-derived natural organic matter on the adsorption of MIB and geosmin by powdered activated carbon - Uzun, Habibullah (Frontiers in Environmental Science, 2025)
Wildfires substantially alter watershed chemistry, increasing natural organic matter (NOM) loads and nutrient fluxes into surface waters, which can stimulate algal blooms and the production of taste and odor (T&O) compounds such as 2-methylisoborneol (MIB) and geosmin. This study investigated the performance of five commercially available powdered activated carbons (PACs) in removing MIB and Geosmin from water impacted by ash-derived NOM. Adsorption experiments were conducted using NOM-free water and wildfire-generated white-ash leachate (WA-L), black-ash leachate (BA-L), and unburned vegetation leachate (UV-L), each with 7.5 mg/L DOC and varying aromaticity and molecular weights (MW) (as indicated by SUVA254 and E2/E3 ratios). Under NOM-free conditions, PACs with significant micropore volumes exhibited exceptional adsorption capabilities. PAC-4, distinguished by its narrow micropores (∼0.15 cm3/g in the 0.54–1 nm range) and high pHpzc (8.7), exhibited the highest uptake of both compounds. The adsorption kinetics revealed that within 60 min, over 80% of MIB and 90% of geosmin were removed by all the carbons. PACs with well-balanced microporosity exhibited the most rapid initial uptake (10–30 min). Under NOM conditions, UV-L led to significant pore blocking because of the presence of high-MW NOM. In contrast, WA-L, which contains smaller and more hydrophobic NOM, caused minimal suppression. Despite NOM suppression, a PAC dose of 20 mg/L enabled all PACs (except mesoporous carbon) to achieve ≥85% MIB and ≥98% geosmin removal in WA-L and partially in BA-L. These results highlight the importance of selecting PACs based on pore structure and surface chemistry, as well as the need to adjust PAC dosage during post-wildfire events.